Performance improvement for epitaxially grown SiGe on Si solar cell by optimizing the back surface field. Issue 10 (21st September 2016) - Li, Dun; Zhao, Xin; Wang, Li; Conrad, Brianna; Soeriyadi, Anastasia; Lochtefeld, Anthony; Gerger, Andrew; Barnett, Allen; Perez‐Wurfl, Ivan
Abstract : This letter reports on the performance improvement of an epitaxially grown SiGe on Si solar cell by optimizing the back surface field (BSF). First, a Si0.18 Ge0.82 on silicon (Si) solar cell was fabricated with a 0.25 μm BSF layer. A 25 mV open‐circuit voltage ( V OC ) improvement was observed on this BSF solar cell compared with the reference solar cell without BSF layer. Then, a Si0.18 Ge0.82 on Si solar cell with double BSF layers was designed and fabricated. The measured efficiency of this solar cell is 3.4% when filtered by a GaAs0.79 P0.21 top cell. To the best of the authors' knowledge, the 3.4% efficiency reported here is the highest efficiency for SiGe on Si solar cells when filtered by a GaAs0.79 P0.21 top cell. The previous best reported efficiency for high Ge composition SiGe on Si solar cell was only 1.7% when filtered by a GaAs0.79 P0.21 top cell. Abstract : III–V on Si tandem solar cell has the potential for lower cost. Efficiency improvement of SiGe on Si solar cell was demonstrated by optimizing the back surface field. This SiGe cell can be used as the bottom cell in a III–V on Si tandem solar cell.